Assessment of Fusobacterium and Leptotrichia among Patients with Premalignant Lesions and Healthy Subjects: A Comparative Study - Aslam, Shazia; Talukdar, Bishwajit; Ingale, Prasad Chandrakant; Sneha, Susmit; Khan, Shahrukh; Haripriya, Varanasi (Journal of Neonatal Surgery, 2025)
Background: Oral premalignant lesions (OPML) are associated with an increased risk of progression to oral cancer. The microbial dysbiosis in the oral cavity has been proposed as a contributory factor in the carcinogenic process. Fusobacterium and Leptotrichia, two anaerobic bacteria, have been implicated in oral and systemic diseases. This study aims to assess the prevalence and concentration of Fusobacterium and Leptotrichia among patients with premalignant lesions and healthy subjects to establish their potential role in disease progression. Materials and Methods: A total of 60 participants were recruited for this comparative study, comprising 30 patients with clinically diagnosed premalignant lesions (Group A) and 30 healthy subjects (Group B). Saliva samples were collected from all participants under sterile conditions. Quantitative Polymerase Chain Reaction (qPCR) was employed to detect and quantify Fusobacterium and Leptotrichia. The data were statistically analyzed using the Student’s t-test, with p-values less than 0.05 considered significant. Results: The mean concentration of Fusobacterium in Group A was 2.35 × 10⁴ CFU/mL, significantly higher than in Group B (0.95 × 10⁴ CFU/mL) (p < 0.001). Similarly, Leptotrichia levels were elevated in Group A (1.85 × 10⁴ CFU/mL) compared to Group B (0.75 × 10⁴ CFU/mL) (p < 0.001). The prevalence of Fusobacterium was 80% in Group A and 30% in Group B, while Leptotrichia was detected in 70% of Group A and 25% of Group B. Conclusion: The findings suggest a higher prevalence and concentration of Fusobacterium and Leptotrichia in patients with premalignant lesions compared to healthy subjects. This microbial dysbiosis may contribute to the pathogenesis and progression of oral premalignant conditions. Further studies are warranted to explore the potential of these bacteria as diagnostic markers and therapeutic targets